Red Rosella Tea and Avocado As Simvastatin Therapy Support Reduce Total Cholesterol - Budi Artini; Elyana Asnar; Ika Yuni Widyawati (Universitas Airlangga, 2017)
Introduction: Hypercholesterolemia is a condition characterized by high levels of total cholesterol in the blood. Many studies have proven that steeping tea rosella and flesh of an avocado can reduce total cholesterol levels. This study was conducted to determine the effectiveness of therapy companion rosella tea and avocado in lowering total cholesterol levels in hypercholesterolemia clients.Methods: This type of research is a quasi-experimental study with pre-post test control group design. The population study was a client with hypercholesterolemia in the working area of menganti health centers. First sample group consisted of nine respondents received the drug Simvastatin 10 mg and rosella tea consumed as much as 2 g 1x / day. The second group consisted of nine respondents received the drug Simvastatin 10 mg and avocado meat weighing 330 grams were consumed 1x / day. The control group consisted of 11 respondents have a drug Simvastatin 10 mg oral 1x daily at night before bed. All groups examined total cholesterol levels before treatment and after treatment on day 15.Results: The results of one-way ANOVA test showed a significant difference between before and after treatment in the first group (p=0,001) and second group (p= 0,005), and there is no significant difference before and after treatment in the control group (p= 0,248). The difference between the three groups showed p= 0.025.Conclusion: The conclusion of this study is giving rosella tea and avocado has the same effectiveness in lowering total cholesterol levels so that health workers can suggest the use of rosella tea and avocado as a companion therapy to reduce total cholesterol level.